Pendampingan Penyusunan Proposal Penelitian Tindakan Kelas dalam Rangka Penguatan Kinerja Guru dan Promosi Jabatan di SMP Negeri 1 Cibadak Rangkasbitung, Lebak - Diana Triwardhani (Jurnal Pengabdian Pada Masyarakat, 2021)
ASSISTANCE IN THE PREPARATION OF CLASSROOM ACTION RESEARCH PROPOSALS FOR STRENGTHENING TEACHER PERFORMANCE AND POSITION PROMOTION AT SMP NEGERI 1 CIBADAK RANGKASBITUNG, LEBAK. This Abdimas aims to provide training and assistance in terms of classroom action research carried out on teachers at SMP Negeri 1 Cibadak Kab. Lebak so that they will get used to making this research which will be used to increase the credit score in the context of promotion so that it will increase their performance and will also be easy for promotion to rank and position. At the beginning, the number of responses was 34 people, but when asked for feedback, only 26 respondents, but they wanted to make classroom action research and were in process, even though none had yet completed the proposal.